1995
DOI: 10.1021/jm00020a005
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antifungal Activity of New Azole Derivatives Containing an N-Acylmorpholine Ring

Abstract: A series of azole derivatives carrying an N-acylmorpholine ring are described. The compounds were chemically designed to simulate the lanosterol D ring, taking advantage of the conformational preferences of 2-alkyl-1-acylmorpholines. Three structural variables, the nature of the N-benzoyl group, the phenyl substituents, and the degree of oxidation at carbon 2 of the morpholine, were optimized for maximum activity. Only the (5R,6R) isomers showed antifungal activity. Cyclic hemiacetal (-)-39a (UR-9746) and cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 6 publications
0
17
2
2
Order By: Relevance
“…In rat systemic infections due to Aspergillus, after an oral dose of 1.0 mg/kg b.i.d., it showed good activity (but less than that of amphoteri- cin B). It is more active than fluconazole in rabbit systemic candidosis [99].…”
Section: Everninomicin (Sch 27899)mentioning
confidence: 94%
“…In rat systemic infections due to Aspergillus, after an oral dose of 1.0 mg/kg b.i.d., it showed good activity (but less than that of amphoteri- cin B). It is more active than fluconazole in rabbit systemic candidosis [99].…”
Section: Everninomicin (Sch 27899)mentioning
confidence: 94%
“…A rota sintética proposta é composta por três etapas, onde a primeira consistiu na acilação de Friedel-Crafts no 1,3difluorobenzeno (3) com o uso de cloreto de α-cloroacetila com catálise por cloreto de alumínio (Esquema 5). 19…”
Section: Resultsunclassified
“…Os carbonos C-1, C-3, C-5 e C-6 apresentaram-se como duplos dupletos com diferentes constantes de acoplamentos. Já C-7 e C-9/9' puderam ser observados como dois dupletos com (J = 5 Hz) em 73,0 e 54,3 ppm, respectivamente.O espectro de RMN19 F mostrou os dois sinais referentes a F-2 e F-4, os quais geraram multipletos em -111,4 e -107,4 ppm devido ao acoplamento com os núcleos de hidrogênio presentes na molécula (Figura 8).…”
unclassified
“…UR-9746 at 10 mg kg ¼ 1 was superior to 1 mg kg ¼ 1 doses, uconazole and controls. were encouraging [6,7]. Both compounds were found to be active in ×itro and in ×i×o against Coccidiodes immitis [9,10], Candida sp.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, there is a reason to search for new and potentially more effective alternatives to uconazole. Two such alternatives are the azoles UR-9751 and UR-9746 (from J. Uriach and Cia, S.A., Barcelona, Spain) [6]. Initial studies in mice suggested that these are ef cacious in murine cryptococcosis [7].…”
Section: Introductionmentioning
confidence: 99%